Erratum: Correction of the authors' list and affiliations to “Specificity of chest computed tomography in COVID-19-associated pneumonia: a retrospective study“ (Almanac of Clinical Medicine, 2021)
Herewith we would like to inform our readers that the final version of the article doi: 10.18786/2072-0505-2021-49-001, published online on 02.03.2021, was replaced with a corrected version on 15.03.2021. The corrected version, according to the authors request, includes the following changes: the author list and the affiliations, authors' contributions, acknowledgements sections.The article should be cited as “Korb TA, Gavrilov PV, Chernina VYu, Blokhin IA, Aleshina OO, Mokienko OA, Morozov SP, Gombolevskiy VA. Specificity of chest computed tomography in COVID-19-associated pneumonia: a retrospective study. Almanac of Clinical Medicine. 2021;49. doi: 10.18786/2072-0505-2021-49-001.